One way is to solve for the inverse of the first function
remember, to solve, replace f(x) or g(x) with y, switch x and y, solve for y and replace it with ![f^{-1} (x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%20%28x%29)
A.
![f(x)=x/2+8\\y=x/2+8\\x=y/2+8\\x-8=y/2](https://tex.z-dn.net/?f=f%28x%29%3Dx%2F2%2B8%5C%5Cy%3Dx%2F2%2B8%5C%5Cx%3Dy%2F2%2B8%5C%5Cx-8%3Dy%2F2)
![2x-16=y](https://tex.z-dn.net/?f=2x-16%3Dy)
![f^{-1}=2x-16](https://tex.z-dn.net/?f=f%5E%7B-1%7D%3D2x-16)
nope, not A
<h3>What is the inverse function?</h3>
The inverse function of a function f is a function that undoes the operation of f. The inverse of f exists if and only if f is bijective, and if it exists, is denoted by ![{\displaystyle f^{-1}.}](https://tex.z-dn.net/?f=%7B%5Cdisplaystyle%20f%5E%7B-1%7D.%7D)
B.
![f(x)=3x^3+16\\y=3x^3+16x=3y^3+16\\x-16=3y^3\\(x-16)/3=y^3](https://tex.z-dn.net/?f=f%28x%29%3D3x%5E3%2B16%5C%5Cy%3D3x%5E3%2B16x%3D3y%5E3%2B16%5C%5Cx-16%3D3y%5E3%5C%5C%28x-16%29%2F3%3Dy%5E3)
![f^{-1}(x)=\sqrt[3]{((x-16)/3)}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Csqrt%5B3%5D%7B%28%28x-16%29%2F3%29%7D)
nope, not the same
not B
C.
![f(x)=18/x-9\\y=18/x-9\\x=18/y-9\\x+9=18/y\\y(x+9)=18\\y=18/(x+9)\\f^{-1}(x)=18/(x+9)](https://tex.z-dn.net/?f=f%28x%29%3D18%2Fx-9%5C%5Cy%3D18%2Fx-9%5C%5Cx%3D18%2Fy-9%5C%5Cx%2B9%3D18%2Fy%5C%5Cy%28x%2B9%29%3D18%5C%5Cy%3D18%2F%28x%2B9%29%5C%5Cf%5E%7B-1%7D%28x%29%3D18%2F%28x%2B9%29)
The correct, answer is C.
To learn more about the inverse function visit:
brainly.com/question/2972832
#SPJ1
<h2>Greetings!</h2>
Answer:
One number is
and the other number is ![\frac{1}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B7%7D)
Step-by-step explanation:
Let x be the smaller number and y be the bigger number.
x = x
y = 5x
6x + 3y = 3
6x + (3 * 5x) = 3
6x + 15x = 3
(÷3)
2x + 5x = 1
7x = 1
x = ![\frac{1}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B7%7D)
6x + 3y = 3
6(
) + 3y = 3
+ 3y = 3
3y = 3 - ![\frac{6}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B7%7D)
3y = ![\frac{15}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B15%7D%7B7%7D)
Divide both sides by 3 to get 1y:
y = ![\frac{5}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B7%7D)
So one number is
and the other number is ![\frac{1}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B7%7D)
<h2>Hope this helps!</h2>
Whole number can be a integer. rational number can not be a integer that is repeating.
A=6a^2
A=6(5.5)^2
A=181.5
Hopefully I answered correctly.
Answer:
2 ounces
Step-by-step explanation:
25/12.5 = 2